Propagação de Guazuma ulmifolia Lam. por miniestaquia - Fonseca, Ruthy Meyre Costa (2016)
Despite the diversity of woody species of flora, there are few studies with vegetative propagation. The improvement of vegetative propagation for native species will contribute to the advancement of forestry in different sectors, including the recovery of degraded areas and environmental preservation. This work aimed to vegetatively propagate Guazuma ulmifolia Lam kind by minicutting technique and specific objectives to evaluate the survival of ministumps.; quantify the production of cuttings due to different concentrations of nutrient solution; measure the survival of cuttings, analyze the adventitious rooting of cuttings due to the presence and absence of IBA (IBA). They were used as ministumps seedlings originated by seminiferous spread obtained from commercial nursery. Seminal minigarden comprised ministumps vasculature in the mineral nutrition of ministumps was applied using a beaker. The treatments were based on variations in the concentrations of the nutrient solution (25%, 50% and 100%). Were three collections of propagules (cuttings) in order to assess the effect of nutritions as productivity minicutting and application of IBA for rooting. To the survival of ministumps was 100% in seminal minigarden after three successive collections of cuttings. The ministumps receiving the solution at a concentration of 100% showed higher productivity minicuttings per square meter per year. After staking the cuttings remained in house heated and automated vegetation. The rooting of cuttings was evaluated at 36, 34 and 35 days, respectively, first, second and third collection. During the execution of the experiment was over 93% survival of minicuttings considering all treatments. Toras living minicuttings rooted, so the survival percentage of them was equal to the roots. For rooting, IBA and different nutrient solution concentrations showed no significant effect at 5% error probability by F test, however, when evaluating collections, they differ significantly. As for radicial force found significant effect between the bud collection, nutrient solution and AIB, nutrient solution and bud collection, AIB and shoot collection and solution, AIB and shoot collection. The minicutting technique can be considered viable for minicutting rooting Guazuma ulmifolia from ministumps produced via seminal.